An Uncertainty Analysis of Temperature Distribution on Loop Heat Pipe Prototype - Nursinta Adi Wahanani; Mukhsinun Hadi Kusuma; Giarno Giarno; Afifa Pramesywari; Dedy Haryanto; Yoyok Dwi Setyo Pambudi (Jurnal POLIMESIN, 2022)
To improve safety and normal operation aspects to be more economical, the NuScale type power reactor has the potential to be added passive cooling system technology. The technology is a loop heat pipe (LHP) with a wick made of a collection of capillary tubes. To determine the thermal performance of the LHP technology properly, the supporting analysis was needed before the experiment is carried out. One of the necessary supporting factors were to know the accuracy of measuring the temperature distribution on the LHP. The objective of this study was to determine the value of the uncertainty of the thermocouple used in the LHP experiment. By knowing the accuracy of the measurement of the temperature distribution, it is hoped that the resulting data is good and accurate. Data measurement was carried out using the National Instruments data acquisition system. The temperature distribution data retrieval was carried out under the condition that the LHP was in a steady state at the temperature of the hot water as the source of the LHP temperature of 35˚C, 45˚C, 55˚C, and 65˚C. Data collection was carried out within approximately 10 hours of the LHP experiment. The recorded temperature distribution data is then compared with temperature data using a well calibrated derived standard thermocouple. The calculation of the uncertainty value is carried out by statistical methods commonly used to determine the uncertainty of the temperature distribution measurement. The measurement results show that the average temperature value obtained is within the range of the standard uncertainty values of the thermocouple used. The uncertainty value obtained at all measurement points on variations in hot water temperature have value below the standard uncertainty value of the derived standard thermocouple used, which is 0.1°C. Based on these results, it can be concluded that the thermocouple used in the LHP experiment is feasible and has very good accuracy so that it can produce accurate and good LHP temperature distribution data.